Pharmaceutical care provision in veterinary pharmacy (Research, Society and Development, 2025)
The role of the pharmacist is recognized and valued in society due to their vast knowledge of pharmacological treatment. With the growing bonds between humans and animals, it becomes necessary for this attention to be expanded to animals as well .The main objective of this article is to present case reports, selected by the authors in which, the diligence of the pharmacist was essential to ensure a satisfactory therapeutic result. Among the reported cases, in 6 (six) of them pharmaceutical care was provided through pharmaceutical counseling, in 3 (three) cases through alterations of pharmaceutical forms (FF), or even identification of incorrect prescriptions as it was done in 2 (two) cases. In this context, a model of service protocol was developed for verifying possible prescription errors and identifying the most appropriate FF, collaborating with pharmacists to conduct individualized and specialized care, as well as having a list of inappropriate medications to avoid dispensing. Therefore, the work reinforces the importance of veterinary pharmaceutical monitoring and the multidisciplinary work carried out between pharmacists and veterinarians, seeking to promote the best treatment and encouraging new studies to be conducted in this area.